2017
DOI: 10.1016/j.jval.2017.08.2153
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Representation Of Patients’ Opinions For Decision-Making: Are Online Health Communities Good Candidates?

Abstract: though it is not recommended for use in paediatric populations. For submission of CUAs to Health Technology Appraisal bodies like NICE, utility values derived from clinical trials is preferred over values obtained from literature as commented by ERG in one of the submissions. Mapping data to EQ-5D from a non-preference based measure using data collected from patients experiencing the treatment of interest is accepted as an alternative within the NICE reference case. ConClusions: In the absence of direct utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Another limitation is the recruitment method, in which only those patients with the ability and competency to use the Internet would be likely to respond to the survey (likely excluding post-stroke and TBI patients with more significant cognitive dysfunction). As mentioned earlier, the Carenity community likely engages younger, female patients, which may account for the younger sample than in other reported surveys (20). This skew to a younger, more cognitively-able sample likely explains the surprisingly high proportion of working patients.…”
Section: Discussionmentioning
confidence: 84%
“…Another limitation is the recruitment method, in which only those patients with the ability and competency to use the Internet would be likely to respond to the survey (likely excluding post-stroke and TBI patients with more significant cognitive dysfunction). As mentioned earlier, the Carenity community likely engages younger, female patients, which may account for the younger sample than in other reported surveys (20). This skew to a younger, more cognitively-able sample likely explains the surprisingly high proportion of working patients.…”
Section: Discussionmentioning
confidence: 84%
“…In 2019, it was estimated that 86.7 percent of people living in developed countries used the internet [ 53 ]. Moreover, it has been shown that Carenity communities, when compared with the SNIIRAM database (a quantified claim database available in France where all individual refunding acts are listed but without any disease-related information), reflect the main characteristics of online users willing to share their experience with a disease, with an over-representation of female patients aged from 25 to 54 [ 54 ]. The study population was based on patients registered on the Carenity platform from Europe and USA and did not include other relevant sampling procedures and methods.…”
Section: Discussionmentioning
confidence: 99%
“…As individuals registered in patient communities may likely be heavily burdened by their condition, our study population may overrepresent highly symptomatic and polymedicated patients. Nevertheless, it has been shown that characteristics of patients in Carenity communities reflect the main characteristics of web-based users willing to share their medical experience but with an overrepresentation of female patients aged 25-54 years [ 32 ]. This study exclusively included patients registered on the French Carenity platform and did not include other relevant sampling procedures and methods.…”
Section: Discussionmentioning
confidence: 99%